2014
DOI: 10.1111/nep.12308
|View full text |Cite
|
Sign up to set email alerts
|

Association of angiotensin type 2 receptor gene polymorphisms with ureteropelvic junction obstruction in Brazilian patients

Abstract: Our results support that the AGTR2 gene may contribute to the pathogenesis of UPJO and the genetic origin of CAKUT could vary according to phenotype expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Single gene-based association studies found polymorphisms in MMP3, BMP4, and AGTR2 to be associated with an increased risk of CAKUT. [86][87][88] High-throughput genotyping technologies allow the rapid genotyping of >1 million SNPs across the whole genome and enable genome-wide association studies (GWAS) in a hypothesis free, unbiased manner. The only study to date that has exploited these advantages conducted a genome-wide TDT analysis in 410 patient-parent trios from Ireland using 643,691 SNPs, as well as a GWAS in 500 unrelated patients with VUR and 851 controls using 580,000 SNPs.…”
Section: Gene-based or Genome-wide Association Studiesmentioning
confidence: 99%
“…Single gene-based association studies found polymorphisms in MMP3, BMP4, and AGTR2 to be associated with an increased risk of CAKUT. [86][87][88] High-throughput genotyping technologies allow the rapid genotyping of >1 million SNPs across the whole genome and enable genome-wide association studies (GWAS) in a hypothesis free, unbiased manner. The only study to date that has exploited these advantages conducted a genome-wide TDT analysis in 410 patient-parent trios from Ireland using 643,691 SNPs, as well as a GWAS in 500 unrelated patients with VUR and 851 controls using 580,000 SNPs.…”
Section: Gene-based or Genome-wide Association Studiesmentioning
confidence: 99%
“…The frequency of the G allele in AGTR2 gene was also higher in CAKUT patients than in the general population in Italian (Rigoli et al, ) and Korean children (Hahn et al, ), while no differences were found in patients from Greece (Siomou et al, ). In this context, our group extended previous findings by increasing the sample size (290 cases and 262 controls) and by testing five SNPs that cover the entire AGTR2 gene (Miranda et al, ). A significant association of AGTR2 gene at rs3736556 and at rs5194 with UPJO were found, while no associations were detected with MCDK and vesicoureteral reflux (VUR) in our Brazilian sample (Miranda et al, ).…”
Section: Hypothesis To the Development Of Cakutmentioning
confidence: 69%
“…In this context, our group extended previous findings by increasing the sample size (290 cases and 262 controls) and by testing five SNPs that cover the entire AGTR2 gene (Miranda et al, ). A significant association of AGTR2 gene at rs3736556 and at rs5194 with UPJO were found, while no associations were detected with MCDK and vesicoureteral reflux (VUR) in our Brazilian sample (Miranda et al, ).…”
Section: Hypothesis To the Development Of Cakutmentioning
confidence: 69%
See 2 more Smart Citations